2005
DOI: 10.1111/j.1399-3046.2005.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved long‐term allograft function in pediatric renal transplantation with mycophenolate mofetil

Abstract: MMF has been shown to decrease the incidence of acute rejection in children and adults at 1 and 3 yr. Other beneficial effects of MMF have been more difficult to demonstrate. Our open‐labeled study presents a 5‐yr data for patients and graft survival, allograft function, and growth in MMF‐treated patients. The trial included 29 patients who were treated with MMF in combination with cyclosporine and methylprednisone. Patients were compared with a preceding group of 29 patients treated with AZA instead of MMF. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
2
21
1
Order By: Relevance
“…In children, the peak concentration of MPA occurs at approximately 2.5 h after the administration of EC-MPS [15] compared to 1-2 h with MMF [16], which is consistent with findings in adult recipients [10]. In patients receiving cyclosporine (CsA), a single-dose pharmacokinetic study of EC-MPS in children aged [5][6][7][8][9][10][11][12][13][14][15][16] years has demonstrated that 450 mg/m 2 of EC-MPS provides similar MPA exposure (area under the curve, AUC) to 600 mg/m 2 MMF [15,16]. There are no data available, however, on the long-term pharmacokinetics of EC-MPS in children.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In children, the peak concentration of MPA occurs at approximately 2.5 h after the administration of EC-MPS [15] compared to 1-2 h with MMF [16], which is consistent with findings in adult recipients [10]. In patients receiving cyclosporine (CsA), a single-dose pharmacokinetic study of EC-MPS in children aged [5][6][7][8][9][10][11][12][13][14][15][16] years has demonstrated that 450 mg/m 2 of EC-MPS provides similar MPA exposure (area under the curve, AUC) to 600 mg/m 2 MMF [15,16]. There are no data available, however, on the long-term pharmacokinetics of EC-MPS in children.…”
Section: Introductionsupporting
confidence: 68%
“…In pediatric renal transplantation, a multicenter trial has demonstrated that drug therapy with the mycophenolate mofetil (MMF) formulation of MPA significantly reduces acute rejection and graft loss relative to that in historical controls receiving azathioprine [4]. While randomized trials in the pediatric population are lacking, other prospective [5,6] and retrospective [7][8][9] studies in children have consistently shown that MMF therapy is effective in preventing acute rejection and associated with good graft survival rates and an acceptable safety profile.…”
Section: Introductionmentioning
confidence: 96%
“…This popularity of mycophenolate reflects its proven efficacy in reducing risk for acute renal rejection and its safety and tolerability profile. The incidence of acute rejection is markedly lower, ranging from 15 to 35%, in patients who received MMF compared with those who received either azathioprine or no antimetabolite in combination with a CNI and corticosteroids (85)(86)(87)(88)(89). MMF has also been found to improve 5-year outcome in pediatric renal transplant recipients and prolong half-life of the graft (90).…”
Section: Pediatric Transplantationmentioning
confidence: 91%
“…Since studies in adult renal transplant recipients had previously established the superiority of MMF over AZA or placebo in reducing the risk of acute rejection, it was important for the pediatric transplant community to have prompt access to open-label studies (12)(13)(14). For a summary of selected published studies of MMF used in combination with CsA and steroids in pediatric renal transplantation, see Table 1 (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: First Studies Evaluating Mycophenolate Mofetil Efficacy and mentioning
confidence: 99%